Larval Stages of Phyllodistomum sp. (Digenea, Gorgoderidae) from the Duck Mussels Anodonta anatina in Ukraine - Kudlai, O.S.; Yanovich, L.N. (Вестник зоологии, 2013)
Rhopalocercous cercariae were found in the gonads of duck mussels, Anodonta anatina (Linnaeus, 1758) collected from the Sluch River (Zhytomyr oblast, Ukraine). The morphological features observed led to conclusion that this species belonged to the genus Phyllodistomum Braun, 1899. Obtained results suggested that the second intermediate hosts in the life cycle of this trematode were absent. Free-swimming cercariae were observed encysting in water. This species is similar to Phyllodistomum pseudofolium Nybelin, 1926 by overall body proportions and ratio of suckers: lengths of oral to ventral sucker 1 : 1.1; widths of the same organs 1 : 1.2. To confirm the taxonomic position of the species found and establish a possible relationship between it and P. pseudofolium an experimental infection of fish Carassius carassius (Linnaeus, 1758) as potential definitive host was performed. The infection was not successful. Descriptions and figures of all detected larval stages of Phyllodistomum sp.are provided.